Fuzzy closure systems: Motivation, definition and properties - Ojeda Hernández, Manuel; De-las-Peñas-Cabrera, Inmaculada; Cordero-Ortega, Pablo; Muñoz-Velasco, Emilio José (Elsevier, 2022)
The aim of this paper is to extend closure systems from being crisp sets with certain fuzzy properties to proper fuzzy sets. The presentation of the paper shows a thorough discussion on the different alternatives that could be taken to define the desired fuzzy closure systems. These plausible alternatives are discarded if they are proven impossible to be in a bijective correspondence with closure operators. Finally, a definition of fuzzy closure system is established and a one-to-one relation with closure operators is proved.
Keywords: Lógica difusa; Fuzzy set; Closure system; Complete lattice; Fuzzy logic; Extensional